TRPC6-Mediated Zn2+ Influx Negatively Regulates Contractile Differentiation of Vascular Smooth Muscle Cells - Chenlin Su; Xinya Mi; Tomoya Ito; Yuri Kato; Akiyuki Nishimura; Ryu Nagata; Yasuo Mori; Motohiro Nishida (Biomolecules)
Vascular smooth muscle cells (VSMCs) can dynamically change their phenotype between contractile and synthetic forms in response to environmental stress, which is pivotal in maintaining vascular homeostasis and mediating pathological remodeling of blood vessels. We previously reported that suppression of canonical transient receptor potential 6 (TRPC6) channel-mediated cation entry sustains VSMCs contractile phenotype and promotes the blood flow recovery after hindlimb ischemia in mice. We also reported that Zn2+, a metal biomolecule mobilized by TRPC6 channel activation, exerts potential beneficial effects on cardiac contractility and remodeling. Therefore, we hypothesized that TRPC6-mediated Zn2+ influx participates in phenotype switching of VSMCs and vascular remodeling. We established rat aortic smooth muscle cells (RAoSMCs) stably expressing wild type (WT) and Zn2+ only impermeable TRPC6 (KYD) mutant. Although the resting phenotypes were similar in both RAoSMCs, pharmacological TRPC6 activation by PPZ2 prevented the transforming growth factor (TGF) β-induced reduction in the intracellular Zn2+ amount and contractile differentiation in RAoSMCs (WT), but failed to prevent them in RAoSMCs (KYD). There were no significant differences in TRPC6-dependent cation currents among all RAoSMCs pretreated with or without TGFβ and/or PPZ2, suggesting that TRPC6 channels are functionally expressed in RAoSMCs regardless of their phenotype. Treatment of mice with PPZ2 attenuated the progression of vascular remodeling caused by chronic angiotensin II infusion. These results suggest that Zn2+ influx through TRPC6 channels negatively regulates the TGFβ-induced contractile differentiation of VSMCs and the progression of vascular remodeling in rodents.